Pathologies caused by lifting moisture on a building in Palms - TO town - Paz, Lidiane Andrade Fonseca Da; Costa, Láylla Cristhine de A.; Paula, Matheus Oliveira de; Almeida, Wagner Júnior Duarte de; Fernandes, Fernando A. da S. (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
This work aims to analyze pathological manifestations caused by moisture in a building in the city of Palmas - TO, which is one of the biggest problems faced during the life of the building, and considering that the conditions are harmful to the building, were identified some possibilities to decrease the same. Held literature and record images taken on the spot, where the diseases occur. After research it was possible to the places of occurrence, pathological manifestations due to moisture on these sites, classify them and provide appropriate solutions. Where it was found that the best control is prevention, which occurs in design, with a good design of pipes, use of quality materials and skilled labor.